Peran Komitmen Afektif terhadap Perubahan sebagai Mediator Hubungan antara Pertukaran Pemimpin-Anggota dengan Kemampuan Mengatasi Perubahan pada Unit Area PT X - Jonathan Permana; Endang Parahyanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The development in the era of digitalization requires companies to make significant changes in their business processes to face competitors and adapt to the environment. This study aims to determine the role of affective commitment to change as a mediator of the leader-member exchange relationship with the ability to coping with change in the PT X Area Unit. Subjects totaled 222 participants from 7 Unit Area PT X. This study uses a quantitative method through online questionnaires, with a non-experimental research design with a correlation design and a mediation analysis of the research variables. The results of the mediation analysis show that affective commitment to change can act as a mediator with a form of full mediation between leader-member exchanges, with an indirect coefficient value of 0.08 with a 95% confidence interval value between 0.03 and 0.15 on the ability to cope with change. The results of study concluded that leader-member exchange can predict the ability of employees to deal with change if employees have an affective commitment to change.